Intraparenchymal Neural Stem/Progenitor Cell Transplantation for Ischemic Stroke Animals: A Meta-Analysis and Systematic Review - Hailong Huang; Kun Qian; Xiaohua Han; Xin Li; Yifeng Zheng; Zhishui Chen; Xiaolin Huang; Hong Chen (Stem Cells International)
Intraparenchymal transplantation of neural stem/progenitor cells (NSPCs) has been extensively investigated in animal models of ischemic stroke. However, the reported therapeutic efficacy was inconsistent among studies. To evaluate this situation, PubMed, Embase, and Web of Science databases were searched for preclinical studies using NSPC intraparenchymal transplantation in ischemic stroke animals. Data of study quality score, neurobehavioral (mNSS, rotarod test, and cylinder test) and histological (infarct volume) outcomes, cell therapy-related serious adverse events, and related cellular mechanisms were extracted for meta-analysis and systematic review. A total of 62 studies containing 73 treatment arms were included according to our criterion, with a mean quality score of 5.10 in 10. Among these studies, almost half of the studies claimed no adverse events of tumorigenesis. The finally pooled effect sizes for neurobehavioral and histological assessments were large (1.27 for mNSS, 1.63 for the rotarod test, 0.71 for the cylinder test, and 1.11 for infarct volume reduction). With further analysis, it was found that the administration time poststroke, NSPC donor species, and transplantation immunogenicity had close correlations with the degree of infarct volume reduction. The NSPC dosage delivered into the brain parenchyma was also negatively correlated with the effect of the cylinder test. Intriguingly, endogenous apoptosis inhibition and axonal regeneration played the most critical role in intraparenchymal NSPC transplantation among the cellular mechanisms. These results indicate that intraparenchymal NSPC transplantation is beneficial for neurobehavioral and histological improvement and is relatively safe for ischemic stroke animals. Therefore, intraparenchymal NSPC transplantation is a promising treatment for stroke patients.